The Relationship of Acculturation, Traumatic Events and Depression in Female Refugees - Starck, Annabelle; Gutermann, Jana; Schouler-Ocak, Meryam; Jesuthasan, Jenny; Bongard, Stephan; Stangier, Ulrich (Frontiers in Psychology, 2020)
Recent research has identified significant correlations between traumatic events and depression in refugees. However, few studies have addressed the role of acculturation strategies in this relationship. This study explored the relationship between cultural orientation, traumatic events and depression in female refugees from Syria, Afghanistan, Eritrea, Iran, Iraq and Somalia living in Germany. We expected acculturation strategies to moderate the effect of traumatic experiences on depression. The sample included 98 female refugees in Germany. The depression scale of the Hopkins Symptom Checklist (HSCL) represented the dependent measure. The trauma checklists derived from the Posttraumatic Diagnostic Scale (PDS) and the Harvard Trauma Questionnaire (HTQ) as well as the Frankfurt Acculturation Scale (FRACC) were used as independent measures for traumatic events and orientation towards the host culture as well as orientation towards the culture of origin, respectively. A moderation analysis was conducted to examine whether the relationship between the number of traumatic events and depression was influenced by the women’s orientation towards the culture of origin and the host culture. We identified a significant model explaining 26.85% of the variance in depressive symptoms (Cohen's f2 = .37). The number of traumatic events and the orientation towards the host culture exerted significant effects on depressive symptoms. The moderating effect was not significant, indicating that the effect of the number of traumatic events was not influenced by cultural orientation. Based on our results, orientation towards the host culture as well as traumatic experiences exert independent effects on depressive symptoms in refugees.